Kinetic and Equilibrium Studies on Removal of Nickel Ions onto Pomegranate Peel - Farhan, Safanah A; Dadoosh, Rasha M; Mahmood, Ayad T (Al-Nahrain Journal of Science, 2018)
In this work, pomegrante peel (PGP) was investigated as adsorbent for removal of nickel ions from aqueous solution. It was found that maximum adsorption occur at PH7. Their equilibrium data were fitted with the Freundich and Langmuir isotherms. The adsorption kinetics data were best fitted with the pseudo–second order